Electrogenerated chemiluminescence emission from cadmium germanate nanoparticles1. Issue 96 (17th October 2015) - Li, Ju; Fang, Yi-Min; Song, Jing; Wang, Ming-E.; Sun, Jian-Jun
<x xml:space="preserve">Abstract</x> This was the first report on the ECL of semiconductor nanocrystals involving three elements and dealt with amorphous nanomaterials.